Hospital Building Maintenance Management Model - Olanrewaju, Abdullateef; Wai Fang, Wong; Yeow Tan, Seong (International Journal of Engineering and Technology, 2018)
Wellness of the patients correlated with the hospital building performance. For building to achieve it design objectives and provide value added services to owners, users and other stakeholders, maintenance functions are strategic. As a result, management of the maintenance of hospital buildings is a delicate and expensive task to perform. Despite the fact that there is a lack of representative data on the maintenance of hospital buildings in Malaysia, there is a growing concern surrounding the subject. Fire outbreaks and decay in hospital buildings suggest a need to conduct critical research to investigate the maintenance management practices of hospital buildings. This paper reports part of an ongoing research that aims to develop a maintenance model for hospital buildings. Hence, this current research reports the results of literature reviews and observations on hospital buildings in Malaysia and their maintenance practices. Upon reviewing the literature, a conceptual framework of maintenance model for hospital buildings was proposed. The research found that the current approaches to maintenance management in the hospital buildings were corrective, fragmented, cost-driven and expensive. The procurement of maintenance services was mainly outsourcings. All these call into question, the decision making processes of the hospital maintenance organisations. Collectively, the above considerations have led to the formulation of the main research question- what are the critical success factors [CSFs] for the maintenance of hospital buildings? The current study also discussed a proposed research methodology for the main research. Furthermore, issues pertaining to the research design, ontology and epistemology were briefly discussed. It was established that to enrich the findings of the main research, it was imperative to collect primary data using both quantitative and qualitative research paradigms.Â